Determination of antioxidant activities, total phenolic content, total flavonoid content and ascorbic acid in pomegranate (punica granatum) and passion (passiflora edulis) fruit peel, seed and juice / Fara Syazana Ahmad Murshid - Ahmad Murshid, Fara Syazana (2013)
The aim of this study is to determine the total phenolic content, total flavonoid content, ascorbic acid content and their antioxidant activities by DPPH and FRAP assays on six samples which are the pomegranate fruit peel, seed, juice, passion fruit peel, seed, and juice. The samples are all extracted by using ethanol to obtain the extracts before the determination of antioxidant content. For total phenolic content, it was determined using Folin-Cioclateu’s reagent with gallic acid as standard and measured at 750 nm. The highest amount of total phenolic content was in pomegranate peel with 182.71 ± 0.57 mg GAE/100 g sample and the lowest was in passion juice with 16.05 ± 0.00 mg GAE/100 g sample. The total flavonoid content was determined at 415 nm with rutin as standard and expressed as mg RE/100 g sample. The highest flavonoid content was in passion peel with 100.94 ± 0.00 mg RE/100 g sample and the lowest was in pomegranate seed with 5.00 ± 0/00 mg RE/100 g sample. Ascorbic acid content was determined according to AOAC method. The highest amount of ascorbic acid was in pomegranate peel with 62.84 ± 10.88 mg/100 g sample and the lowest was in passion seed with 15.71 ± 5.44 mg/100 g. Each sample was treated with DPPH and FRAP assay for the determination of antioxidant activities in each components and all the samples exhibited good antioxidant activities indicates the presence of antioxidant in the samples. All the samples values have significant difference at (p<0.05). Among the three components in pomegranate fruit, the peels shows the highest antioxidant capacity and activity, while for passion fruit, the peel also shows the highest antioxidant capacity and activities compared to its seed and juice